1960
DOI: 10.1111/j.1151-2916.1960.tb14326.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria in the System ZnO—TiO2

Abstract: The system ZnO-Ti02 has been investigated using quenching, hydrothermal, strip-furnace, and solid-state-reaction techniques. Two compounds were found: Zn2Ti04, which melts congruently at 1549"C., and ZnTiOs, which dissociates hydrothermally at 945°C. to give Zn2Ti04 and rutile. Two eutectics were found: one between ZnO and Zn2Ti04 at 32 mole % TiO, and 1537°C. and the other between ZnzTiOl and TiO? at 58 mole yo Ti02 and 1418°C. Rutile was the only modification of TiO, observed. The reported melting points of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
124
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(135 citation statements)
references
References 18 publications
2
124
0
3
Order By: Relevance
“…The EPMA analysis entirely supports the result. Usually, loss of ZnO becomes significant during heating above 1100°C by volatility, 42 thus experimental chances of Zn substitution to an oxide is often limited. Perhaps, the high-pressure condition might allow us to reduce the ZnO volatility during heating, resulting in the successful Zn substitution to LaFeAsO 0.85 .…”
Section: Resultsmentioning
confidence: 99%
“…The EPMA analysis entirely supports the result. Usually, loss of ZnO becomes significant during heating above 1100°C by volatility, 42 thus experimental chances of Zn substitution to an oxide is often limited. Perhaps, the high-pressure condition might allow us to reduce the ZnO volatility during heating, resulting in the successful Zn substitution to LaFeAsO 0.85 .…”
Section: Resultsmentioning
confidence: 99%
“…Basic studies regarding the phase diagram and the physical properties of ZnO-TiO2 system have been published since 1960s [1,2]. Much attention has been still paid because of its diverse electrical and chemical properties, leading to the wide applications in sensors, microelectronics and high performance catalysts [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the zinc titanate ceramics have been promisingly reported as microwave dielectric materials due to their stable and proper dielectric properties [7][8][9]. Dulin and Rase [1] showed that three compounds exist in the ZnO-TiO 2 system, including Zn 2 TiO 4 (cubic), ZnTiO 3 (hexagonal), and Zn 2 Ti 3 O 8 (cubic). Zn 2 TiO 4 phase can easily be prepared by conventional solid-state reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Dijagram stanja sistema ZnO-TiO 2 još od 1960. godine [49] privlači pažnju istraživača upravo zbog njegovog značaja za praktičnu primenu (sl. 1.14.).…”
Section: Dijagram Stanja Sistema Zno-tiounclassified
“…1.14. Dijagram stanja sistema ZnO-TiO 2 [49] Detaljno proučavanje električnih svojstava ovih materijala dovelo je do njihove široke primene u čvrstim oksidnim gorivim ćelijama, gasnim senzorima, mikroelektronici i katalizatorima visokih performansi za kompletnu oksidaciju ugljen-monoksida i redukciju azot-monoksida [62][63][64].…”
Section: Dijagram Stanja Sistema Zno-tiounclassified